2021
DOI: 10.1080/14760584.2021.1969231
|View full text |Cite
|
Sign up to set email alerts
|

From infection to vaccination: reviewing the global burden, history of vaccine development, and recurring challenges in global leishmaniasis protection

Abstract: Introduction: Leishmaniasis is a major public health problem and the second most lethal parasitic disease in the world due to the lack of effective treatments and vaccines. Even when not lethal, leishmaniasis significantly affects individuals and communities through life-long disabilities, psychosociological trauma, poverty, and gender disparity in treatment.Areas covered: This review discusses the most relevant and recent research available on Pubmed and GoogleScholar highlighting leishmaniasis' global impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 227 publications
0
20
0
Order By: Relevance
“…Leishmaniasis is a major public health problem and the second most lethal parasitic disease, after malaria. In 2016, WHO reported that more than one billion people lived in Leishmania endemic regions and that every year 1 million CL, 300,000 VL, and 20–50,000 lethal VL cases occur [ 2 ] (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Leishmaniasis is a major public health problem and the second most lethal parasitic disease, after malaria. In 2016, WHO reported that more than one billion people lived in Leishmania endemic regions and that every year 1 million CL, 300,000 VL, and 20–50,000 lethal VL cases occur [ 2 ] (and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Several gene targets have been selected for defined attenuated Leishmania vaccines, such as dhfr, lpg2, cpa, cpb, Ufm1, p27, SIR2, BT1, HSP70, centrin, and the paraflagellar rod-2 locus [227,[230][231][232]. However, genetically modified vaccines showed varying degree of stability and protection in animal models [227,233]. L. major dihydrofolate reductase-thymidylate synthase (DHFR-TS) gene knock-out was the first to be tested against virulent L. amazonensis and L. major infections as a potential vaccine [234,235] in susceptible and resistant murine models, but failed to confer protective immunity in rhesus monkey [236].…”
Section: Live Attenuated Vaccinementioning
confidence: 99%
“…The recent application of CRISPR-cas9 technology in Leishmania provides opportunities to introduce gene modifications/deletions creating parasite strains lacking specific antigens, a valuable tool to assess the importance of putative virulence factors and to formally distinguish between bystander and antigen-specific immunity following vaccination. In addition, CRISPR-cas9 underpins the development of live GA Leishmania vaccines [ 33 ].…”
Section: Roadblocks Along the Path To Vaccine Developmentmentioning
confidence: 99%
“…A new generation of live genetically attenuated (GA) vaccines for leishmaniasis have now been developed, showing great promise in experimental models [ 31 ], including cross protection by a L. major centrin −/− vaccine against vector-transmitted L. donovani infection in hamsters [ 32 ]. These are discussed more fully elsewhere [ 33 ]. Second-generation subunit vaccines (including peptides and proteins in a variety of adjuvant and delivery systems [ 34 ];) have shown promise in various experimental models of cutaneous and visceral leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%